ANALISA SISTEM KERJA SENSOR PROXIMITY INDUCTIVE PADA ALAT PENYORTIR BARANG LOGAM DAN NON – LOGAM BERBASIS PLC GLOFA G7M – DR4040A - Endro Mussi, Muhammad; Anisah, Masayu; Damsi, Faisal (JURNAL TELISKA, 2023)
Various kinds of technology have sprung up so that humans can use it in everyday life. Automation systems have become a very important need in the industrial world to improve quality and quantity in production. By designing tools with automation systems, for example, in metal and non-metal goods sorters. Broadly speaking, the company wants maximum production results so that it can satisfy their consumers, so this automation system is needed to make the desired special specifications. Simulation of a metal and non-metal goods sorter using proximity inductive sensors that move goods from the initial place to the intended place using a conveyor, with a drive system to move goods to storage using pneumatic transport to raise or lift goods, is the function of the tool to move goods based on metal and non-metal materials.